Liquid Chromatography–Tandem Mass Spectrometry–Based α1-Antitrypsin (AAT) Testing: A Retrospective Evaluation of a Clinical Algorithm to Detect AAT Deficiency. Issue 4 (21st October 2020) - Murray, Josiah D; Willrich, Maria A; Krowka, Michael J; Bobr, Aleh; Murray, David L; Halling, Kevin C; Graham, Rondell P; Snyder, Melissa R
Abstract: Objectives: Failure to produce sufficient quantities of functional α1-antitrypsin (AAT) can result in AAT deficiency (AATD) and significant comorbidities. Laboratory testing plays a vital role in AATD, with diagnosis requiring documentation of both a low AAT level and a mutated allele. This retrospective evaluation examines the efficacy of a liquid chromatography–tandem mass spectrometry (LC-MS/MS) (proteotyping)–based algorithm for AATD detection. Methods: A 16-month retrospective data analysis was performed on two cohorts: 5, 474 samples tested with the proteotype-based algorithm and 16, 147 samples directly tested by isoelectric focusing (IEF) phenotyping. Results: LC-MS/MS reduced the rate of IEF testing by 97%. The 3% of cases reflexed to IEF resulted in 12 (0.2%) additional phenotype findings. Retrospectively applying the proteotype-based algorithm to the IEF cohort demonstrated a 99.9% sensitivity for the detection of deficiency-associated phenotypes. Most deficiency phenotypes missed by the proteotyping algorithm would come from heterozygous patients with an F, I, or P paired to an S or Z. In all of these cases, patient AAT levels were greater than 70 mg/dL, above the threshold for AAT augmentation therapy. Conclusions: The proteotype algorithm is a sensitive and cost-effective approach for the diagnosis of clinical AAT deficiency.